2005
DOI: 10.1536/ihj.46.1083
|View full text |Cite
|
Sign up to set email alerts
|

<b>Newly Diagnosed Acute Aortic Dissection</b>

Abstract: SUMMARYThe objective of the present study was to examine cases of acute aortic dissection in order to analyze the clinical and diagnostic findings, and to summarize their treatment modalities, as well as their hospital outcomes.Between July 1998 and June 1999, we prospectively studied patients who were newly diagnosed as having acute aortic dissection at 25 hospitals in Mie prefecture. These cases were examined for their demographics, the characteristics of the clinical findings, diagnostic methods, treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Advanced diagnostic techniques, such as computed tomography and echocardiography, may have contributed to the increased incidence of AD. 13 , 14 However, the true incidence of AD is difficult to estimate. Many patients die before reaching a hospital or receiving an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced diagnostic techniques, such as computed tomography and echocardiography, may have contributed to the increased incidence of AD. 13 , 14 However, the true incidence of AD is difficult to estimate. Many patients die before reaching a hospital or receiving an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Population studies published in the late 20 th century reported an incidence of thoracic aorta aneurysms (TAAs) from 5.9 to 10.4 per 100,000 person-years (6,7) and aortic dissection from 2.9 to 4 per 100,000 person-years (8)(9)(10)(11). However, improvements in imaging technology and a higher quotient of older patients have affected these rates, with reported rates as high as 24.4 per 100,000 persons in 2016 (12).…”
Section: ' Introductionmentioning
confidence: 99%
“…Pathologic studies have confirmed that arterial remodeling and media degeneration are the basic vascular structural changes in hypertension 3 . Moreover, the suddenly increased blood pressure will exert an abnormal shear force on the arterial wall, which may cause disruption of the degenerated media and eventually lead to the occurrence of AD 4 . The diameter of the arterial lumen is generally considered an indicator of arterial remodeling 5 .…”
mentioning
confidence: 99%
“…3 Moreover, the suddenly increased blood pressure will exert an abnormal shear force on the arterial wall, which may cause disruption of the degenerated media and eventually lead to the occurrence of AD. 4 The diameter of the arterial lumen is generally considered an indicator of arterial remodeling. 5 With the aortic diameter increasing, the risk of AD increases accordingly.…”
mentioning
confidence: 99%